Cost-utility of aripiprazole once-monthly versus paliperidone palmitate once-monthly injectable for schizophrenia in China - Yiping An; Gang Fang; Zhipeng Pi; Yumeng Zhang; Wei Li; Jinxi Ding (PLoS ONE, 2025)
Objectives From the perspective of Chinese healthcare system, this study compared the cost-utility of aripiprazole once-monthly (AOM) and paliperidone palmitate once-monthly injectable (PP1M) in the treatment of adult patients with schizophrenia in China. Methods A 5-state Markov model was developed to evaluate the cost-utility of 10 years of long-acting injections (LAI) treatment for schizophrenia. The long-term costs and quality-adjusted life years (QALYs) were estimated, with the incremental cost-effectiveness ratio (ICER) as the primary outcome. The annual discount rate was set at 5%. A cost-effectiveness threshold (CET) of 0.51 times China’s 2023 gross domestic product (GDP) (US$ 6,394.536) was used to judge the economics of intervention. Results The current price of AOM in China is relatively high (US$418.140). To assess its cost-effectiveness in the context of potential price negotiations with China Healthcare Security Administration (CHS) for inclusion in the National Reimbursement Drug List (NRDL), we simulated a 40% price reduction (US$257.619). At a CET of 0.51 times GDP per capita (US$6,394.536), the base-case analysis showed that the incremental costs of AOM relative to PP1M after 10 years of treatment were US$1,926.373 with an incremental gain of 0.306 QALYs. The ICER for AOM was US$6,285.303 per QALY, which is below the CET, indicating that AOM is cost-effective. One-way sensitivity analysis identified AOM’s drug cost as the parameter with the greatest impact on results. Probabilistic sensitivity analysis revealed that with a 40% price reduction, the probability of AOM being cost-effective is only 41.70%. However, with a 60% price reduction, AOM became dominantly cost-effective, with the probability increasing to 100%. When the CET was relaxed to 0.90 times GDP per capita (US$11,284.476), the probability of cost-effectiveness for AOM after a 40% price reduction rose to 85.10%. Scenario analyses conducted over a time horizon extending from 10 to 30 years showed that the ICER decreased significantly with longer follow-up, gradually approaching the 0.51GDP threshold and remaining below the 0.90 GDP threshold throughout the analysis. Conclusions The cost-effectiveness of AOM relative to PP1M is highly influenced by its price and the CET. Healthcare decision makers or clinical users need to balance innovation incentives and accessibility.